IDDF2020-ABS-0060 Impact of prior tenofovir disoproxil fumarate (TDF) treatment duration on tenofovir alafenamide (TAF) safety profile in virally suppressed chronic HBV patients switched from TDF to TAF. (18th November 2020) - Yuen Chan, Henry Lik; Lampertico, Pietro; Ahn, Sang Hoon; Fung, Scott; Bae, Ho; Ramji, Alnoor; Lee, Jung Sung; Shafran, Stephen; Gordon, Stuart; Phan, Charles; Tan, Susanna; Flaherty, John; et al.
Abstract : Background: TAF demonstrated noninferior efficacy to TDF with a superior bone and renal safety profile, in viremic chronic HBV (CHB) patients through week 96, and in virally suppressed patients switched from TDF to TAF at 48 weeks. The duration of prior TDF therapy may influence the degree and rate of recovery of bone and renal function following switch to TAF. Here, we evaluate the impact of prior TDF treatment duration on the safety profile of TAF in virally suppressed patients. Methods: In a double-blind, randomized, multicenter, active-controlled, Phase 3 study, 488 CHB patients who were virologically suppressed on TDF for 1 year, and on TDF monotherapy for 6 months were randomized 1:1 to switch to TAF or continue TDF for 48 weeks. In patients originally randomized to receive TAF, renal, bone, and lipid parameters were categorically evaluated by the duration of prior TDF treatment: Results: Of the 243 patients switched to TAF from TDF, 105 (43%) and 138 (57%) had received TDF for 50 years, 74% male, 80% Asian, median eGFRCG 91 mL/min, 4% and 12% had osteoporosis at hip and spine, respectively. Similar changes in renal, bone, and lipid parameters following 48 weeks of TAF treatment were observed by TDF treatment duration. A comparable increase in median eGFRCG, decreases in tubular biomarkers (beta-2 microglobulin/creatinine ratio, retinol binding protein/creatinine ratio), increases in mean percent change in hip and spine BMD, and decreases in bone turnover markers (C-type collagen sequence, procollagen type 1 N-terminal propeptide) were observed among patients previously treated with <4 and ≥4 years of TDF, respectively (table 1 ). Changes in fasting lipid parameters were not influenced by treatment duration. Conclusions: In virally suppressed patients on TDF a median of 4 years who switched to TAF treatment, improvements in bone and renal parameters and changes in fasting lipids were not impacted by prior duration of TDF use.